CHANGES IN THE COMPOSITION OF MARE'S MILK DUE TO THE EFFECT OF ANIMAL’S AGE (PARITY) - Gregić, Maja; Baban, Mirjana; Mijić, Pero; Gantner, Vesna; Bobić, Tina (Works of the Faculty of Agriculture and Food Sciences University of Sarajevo, 2026)
Mare's milk is traditionally used in the regions of Central Asia by nomadic people. Also, there is a long history of utilisation and processing of mare's milk. Furthermore, in recent decades, mare's milk has been researched as a functional food throughout Europe. The production of mare's milk is highly demanding. Since the composition of the mare's milk depends on various factors, the aim of the work was to determine the variability of the composition of the Lipizzaner mare's milk regarding parity. Mare's milk was collected from the 16 Lipizzaner mares bred at a stud farm in eastern Croatia. Regarding parity, the mares were classified into two groups: (A) younger (first to third lactation, n = 8) and (B) older (over third lactation, n = 8). It was found that the amount of milk fat and lactose is higher in the milk of older mares, while the amount of protein was lower in the same animals. Concerning the aspect of functional food in the human diet, protein represents the most important component of mare's milk. Therefore, it can be concluded that the milk of the younger mares is richer in protein and more recommended as a functional food.